Prenatal diagnosis of Pallister-Killian syndrome in pregnancy with normal CVS result and abnormal ultrasound findings in the second trimester - Frisova, Veronika; Svobodova, Ivana Tutkova; Tozzi, Michaela; Raskova, Dagmar (Taiwanese journal of obstetrics & gynecology, 2018)
OBJECTIVE: To highlight importance of detailed ultrasound examination in fetuses with known normal karyotype (and micro-array result) from CVS. In case of markedly abnormal ultrasound result repeated karyotyping by amniocentesis should be considered. Sample should be analyzed by routine cytogenetic techniques, however also micro-array and targeted FISH should be added in order to achieve most accurate diagnosis. CASE REPORT: We report prenatal diagnosis of Pallister-Killian Syndrome (PKS) at 18 gestational weeks. The mother asked us for second opinion scan in our centre due to finding of seven soft markers of chromosomal defects in fetus with normal CVS result. Our examination revealed asymmetrical fetal growth, normohydramnion, spastic fetal movements and several abnormalities: nuchal edema, mild bilateral hydronephrosis, omphalocoele and facial anomalies. We asked for targeted genetic analysis for PKS. Amniocentesis with repeated genetic analysis confirmed PKS (80% mosaicism of tetrasomy 12p). CONCLUSION: Diagnosis of PKS led mother to terminate pregnancy.
Keywords: Ultrasonography, Prenatal; Pregnancy; Humans; Chromosome Disorders; Pregnancy Trimester, Second; Mosaicism; Prenatal Diagnosis; gestační stáří; Female; Micro-array; dospělí; ultrasonografie prenatální; odběr choriových klků; amniocentéza; lidé; Chromosomes, Human, Pair 12; Pallister-Killian syndrome; Amniocentesis; druhý trimestr těhotenství; Adult; ženské pohlaví; 2D-3D ultrasound; mozaicismus; Chorionic Villi Sampling; prenatální diagnóza; těhotenství; lidské chromozomy, pár 12; genetické testování; Genetic Testing; chromozomální poruchy; FISH; Gestational Age; Prenatal diagnosis